3D boron/nitrogen dual doped layered carbon for 2 V aqueous symmetric supercapacitors. (December 2021) - Wei, Feng; Lv, Yaohui; Zhang, Shouquan; Zheng, Jiandong
Abstract: The operating voltage for supercapacitors (SCs) in alkaline electrolyte was limited by the splitting of water. Therefore, it is still a huge challenge to obtain high energy density by improving the operating voltage for aqueous symmetric SCs. Herein, a novel strategy is developed to construct the 3D boron/nitrogen dual doped layered carbon (BNLC) by using the in-situ potassium tetraborate activation from biomass. The synergetic effects of B/N heteroatoms and 3D layered structures enhance the electron transport property, and achieve the high voltage window of 2 V for SCs in 3 M Zn(CF3 SO3 )2 aqueous electrolyte. As a result, the BNLC presents high specific capacitance of 315.3 F g −1 at 0.05 A g −1, good rate performance of 241.1 F g −1 at 40 A g −1 and excellent cycle stability with 98.4% of initial capacitance after 20, 000 cycles. In addition, the energy density of BNLC-based SC in neutral electrolyte (43.8 Wh kg −1 ) is 4.4 times as high as that of BNLC-based SC in alkaline electrolyte (9.9 Wh kg −1 ). This work pioneers an efficient strategy for the use of the synergetic effects of heteroatoms and neutral electrolyte to enhance the energy density of energy storage devices.